- #1

NCStarGazer

- 7

- 0

F=G*(M*m)/r^2

and centripetal force

F = ((V^2)/r)*m

If you set the two equal and solve for G you get:

G = ((V^2)*r)/M

Substituting (4*pi^2*r^2)/T^2 for V^2 you now have

G = (4*pi^2*r^3)/(M*T^2)

With solution for G, look at Kepler's law with Newton's update,

(M+m)*P^2 = (4*pi^2*a^3)/G

Substituting the G solved for into Kepler's equation and consider working with a perfect circle, r will equal a and T will equal P.

Now, once you substitute in the solved G, simplify...

You Get

(M+m)*P^2 = P^2*m

This is obviously not true!

Please let me know where the error is in my observation.

Thanks!